Dimension, Content, and Role of Platform Psychological Contract: Based on Online Ride-Hailing Users - She, Shengxiang; Xu, Haoran; Wu, Zehong; Tian, Yunzhang; Tong, Zelin (Frontiers in Psychology, 2020)
Online platform is a new form of enterprise organization, which makes the interaction between platform and users present new patterns and characteristics. This research focuses on the platform of online car-hailing. On the basis of integrating the relevant research of existing psychological contract, it explores the dimension and content of psychological contract of online car users through interviews, questionnaires and other methods. The results show that the psychological contract of online car users includes two dimensions: transactional psychological contract and relational psychological contract. Moreover, the user's relational psychological contract to the platform is different from that of the traditional enterprise. In addition, this study examines the impact of psychological contract breach on platform relationship quality. The results show that both psychological contract breaches are negatively correlated with platform relationship quality, and the value-added validity of relational psychological contract breach on platform relationship quality is higher.